Democratização do acesso à justiça: um estudo sobre a atuação extrajudicial das Defensorias Públicas - Faustino, Marcella Raphaella (2020)
The debate regarding the need to expand access to justice beyond access to the Judiciary has shown to be essential in both social and academic scopes. As known, a significant portion of the population can’t see their demands solved by judicial instances for a variety of factors, among which the uneven distribution of its agencies inside the national territory, the absence of financial resources and the lack of knowledge by the general public of their own rights stand out. The Public Defense has the mission of overcoming some of these difficulties. This institution, that strives to ensure the hyposufficient are granted access to justice, has the function of ensuring not only the access to judiciary instances but also the enforcement of rights and the solution of controversies outside them as well. Although it has a fundamental role in society’s transformation, the difficulties faced by the Public Defense in meeting all the demands directed at it are visible. Within this scenario, the institution, which is part of the Brazilian justice system, has sought to expand its collective operations and its extrajudicial operations. The current work focuses on analyzing the degree of importance that the State Public Defense, the Federal District Public Defense and the Union Public Defense have been giving to extrajudicial methods of conflict solving, ampliation and consolidation of rights and, consequently, how they have contributed to the democratization of access to justice. Starting from the national scenario, the current work aims to analyze the extrajudicial actuation of the state of Minas Gerais’s Public Defense, as a case study, looking to observe the similarities of its procedures with the rest of the Public Defenses along with its particularities. To start the research, a bibliographic survey on these themes was performed: access to justice, adequate conflict solving methodologies and constitution of Public Defense in Brazil. Posteriorly, aiming to construct an overview of the performance of Public Defense, a preliminary data collection on each Public Defense’s website and their respective Superior Schools’ websites was performed. Furthermore, data from publications made by the National Justice Council, the National Public Defenders Association and the Justice Forum were obtained. Based on the collected data, an open questionnaire was prepared and sent to all Public Defenses of the country. Moreover, a semi-structured interview script was employed to obtain data from the Public Defense of Minas Gerais, chosen as a case study because of its accessibility. Altogether 15 public defenders and the auxiliary coordinator of the Conciliation Center were interviewed. The obtained data suggest that despite the Public Defenses’ recognition of the importance of ampliation of their extrajudicial actions, they still don’t prioritize these activities. Therefore, these institutions can’t promote access to justice in its broad sense since their efforts are focused on their performance within legal procedures. It is noteworthy that the current interdisciplinary research has contributed to the debate regarding the panorama of access to justice in Brazil and how it has enlarged its inequalities. Furthermore, it collaborated for the discussions regarding the use of complementary means of conflict resolution. Finally, it has provided an overview of the employed methods and faced difficulties by the Brazilian Public Defenses, presenting relevant elements for the discussion surrounding the improvement of the offered services. Given the breadth of this theme, the difficulty accessing all the country’s Public Defenses’ data and the changes which these institutions go through, new studies are suggested regarding this theme, collecting further data, aiming to promote the constant debate regarding the actuation of these institutions.